Physical activity and depression - Wojtasik, Monika; Żak, Katarzyna; Załóg, Adam; Nowak, Maria; Pietryszak, Edyta; Kulej, Wojciech; Szołtek, Paulina; Pardela, Rafał; Paruzel, Marcel; Łęcka, Martyna (Journal of Education, Health and Sport, 2025)
This article aims to present the significance of physical activity as a key element in the prevention and therapy of depressive disorders. Through a review of the latest scientific research findings, the article focuses on the role of regular physical activity in reducing the risk of depressive disorders and its effectiveness in the therapeutic process. Various aspects of physical activity are analyzed, such as the type and intensity of training, their impact on neurobiological and psychosocial functions. The article discusses the benefits of physical activity, including mood improvement, reduction of depressive symptoms, and overall well-being enhancement. Furthermore, attention is drawn to the biological mechanisms that may underlie the positive impact of physical activity on mental health. In a therapeutic context, the article examines how physical activity can be an effective complement to traditional methods of treating depression, both pharmacological and psychotherapeutic. The importance of adapting training programs to individual needs and preferences of patients is also emphasized. As a result, the article provides a comprehensive overview of current knowledge regarding the role of physical activity in the prevention and therapy of depressive disorders, with the hope of inspiring further research and refining intervention strategies in the field of mental health.